Optimal design of straight- run gasoline conversion on zeolite catalyst; Petroleum and Coal; Vol. 58, iss. 7 - Samborskaya M. A. Marina Anatolievna; Gryaznova I. A. Inga Andreevna; Mashina V. V. Vera Vadimovna; Cherednichenko O. A. Olga Alekseevna (2016, 2016)
Title screen